Implementasi Konsep Ekonomi Biru Pada Masyarakat Pesisir di Dusun Pandanan, Desa Malaka, Lombok Utara - Rosyada, Vivian; Fitriani, Rahmah; kurniawan, Liyondi; Anggajaya, Leonnardo Suryasyaputra; Arifin, Elma Syaharani; Hikmah, Lailatul; Idris , Ismi Usman; Fitrahadin , Sabda; Waqi'ah , Galuh Raudhatul; Aini, Zafiirah Quratul; Mahendra , Made (Jurnal Wicara, 2025)
Blue economy is a development concept that utilizes marine resources in a sustainable manner to drive economic growth, create jobs, and maintain marine ecosystems. Pandanan Hamlet is one of the coastal areas located in Malaka Village, Pemenang District, North Lombok, which has great potential in the implementation of the blue economy. The implementation of the blue economy in Pandanan Hamlet can be one of the efforts to preserve the environment and the welfare of the local community. Therefore, this study aims to determine the potential of the marine sector and the form of application of the blue economy concept to community welfare in Pandanan Hamlet, Malacca Village, Pemeneng, North Lombok. This research was conducted using descriptive qualitative methods. The Pandanan Hamlet community has quite a lot to take advantage of the potential of the coast and sea by providing various water rides, snorkeling and diving facilities, to the processing of catches into grilled fish and shredded fish innovation. It can be concluded that the hamlet has applied the concept of blue economy to the activities of its coastal communities